Usage Features of Elements of Armenian Culture in a Graphic Design Forum Context - Gyodakyan, Meri; Tuysuzyan, Tamara (Scientific Papers of National University of Architecture and Construction of Armenia, 2024)
The article considers on the rational use of traditional Armenian elements in graphic design forum. There are presented similar events implemented in Armenia and the forums held abroad. The aim of the article is to integrate traditional culture and modern civilization, making contemporary Armenian design distinctive and internationally recognized. The study and inclusion of the Armenian cultural element in the forum serves for different purposes: including educational and cultural programs, participating in other aspects of Armenian history, art and culture, as well as various trends in graphic design. The inclusion of the national element in the graphic design contributes to the presentation of their diversity, showing the uniqueness of the Armenian heritage.